An Analysis of Gender Performativity in the Film Lovely Man - Herryono Soegiarto (Insan Kreasi Media, 2025)
Teddy Soeriaatmadja's film Lovely Man (2011) presents a nuanced depiction of gender performativity through the protagonist, Ipuy, a transvestite confronting societal shame while navigating his relationship with his daughter, Cahaya, who adheres to heteronormative standards. This study seeks to examine the representation of gender performativity in the film through the lens of Judith Butler's theory, which posits that gender is not an inherent quality but a construct that is perpetually enacted and negotiated within daily life. The employed research method is qualitative analysis, utilizing a critical discourse analysis methodology with an examination of representation within the film. The study's findings indicate that Ipuy's gender identity is not static, but is expressed variably depending on the social setting. Within the transvestite and sex worker subculture, Ipuy's gender presentation is embraced; nevertheless, in familial and broader societal contexts, his identity is repudiated and socially stigmatized. This film critiques the notion of gender binary by illustrating how Ipuy, despite embracing his feminine identity, retains elements of masculinity in his paternal role. Consequently, Lovely Man serves as both an exploration of the intricacies of gender identification and a critique of the inflexibility of societal gender conventions.